Evaluation of Alternative Components in Growth Media of Lactobacillus brevis for Halal Probiotic Preparation - Pratiwi, Riyona Desvy; Zanjabila, Sabighoh; Fairuza, Dian; Aminah, Aminah; Praharyawan, Swastika; Fuad, Asrul Muhamad (BRIN, 2020)
Probiotic has been widely used in functional food because of numerous advantages for health. MRS broth is commonly used as standard medium in studying lactobacilli. However, in some communities - like muslim and vegetarian society, components in MRS broth/medium become an issue. Beef extract and peptone – animal derived substances as nitrogen sources in the MRS medium should be avoided for the vegetarian. Meanwhile, for the muslim society, all components must be halal-certified including those animal derived ingredients. Therefore, several alternative sources for beef extract and peptone substitution were studied. Combination of alternative nitrogen sources was applied. In order to increase the effect of the alternative nitrogen sources, alternative carbon sources were also included. This is the first report about effects of L. brevis media components on cells growth to expression level of surface layer protein (Slp). Whey, lactose, sucrose, and galactose showed high contribution to L. brevis growth. However, the tested concentration of those substances were not sufficient to obtain equal bacterial growth and Slp expression than that of MRS broth. In addition, yeast extract appeared necessary to maintain cell wall and Slp expression.